The guarantees for the participation of children and adolescents in the judicial process - Cárdenas Puente, Teresa (2021)
Among the fundamental values of the child protection system, apart from the right to non-discrimination, the right to life and the best interests of the child is the right to child participation in the judicial process; however, this right has not been implemented concretely and adequately to guarantee its effectiveness. In this article, we will examine this right in the legal system and the various normative dispositions that regulate it and identify some issues that highlight the guarantees that should exist for it to be effective. Based on this, we will propose procedural measures to guarantee this right of participation and the full protection of the rights recognized in the Convention on the Rights of the Child, trying to ensure that the intervention is the least harmful as possible, depending on what the circumstances require.